(untitled) (Communications in Computational Physics, 2007)
The velocity slip and temperature jump in micro-Couette flow are investigated with the lattice Boltzmann method (LBM). A new slip boundary condition with the non-equilibrium extrapolation scheme is used in a thermal lattice Boltzmann model (TLBM) where double distribution functions are used to simulate the velocity and the temperature fields in order to capture the velocity slip and the temperature jump of the wall boundary. The simulated velocity and temperature profiles are in good agreement with the analytic results, which shows the suitability of the present model and the new boundary treatment for describing thermal microflows with viscous heat dissipation.